PERANCANGAN SISTEM INFORMASI ABSENSI DI PT. BRAINCODE SOLUTION - Gustiana, Iyan (2086-4221, 2012)
The increase in  the number of employees  should be appropriate with improved service facilities  and amenities  adequate system  performance is expected  to occur. Likewise, the absence facilities that seem trivial but it will have a serious impact if not addressed seriously. NIK input process with a certain length of time in the size range by the number of  queue  to do the  same.  It keeps  the pressure  psychological and  cause errors  in  inputting NIK  itself  .  The reason  and  purpose of  the research  is to design information systems  that have  an integrated  database  in the HR and  payroll  so that attendance data can be processed. The methodology uses a systems structured methode. The result is an information system with an integrated database.